2006
DOI: 10.1210/jc.2005-2379
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Selective Progesterone Receptor Modulator Asoprisnil (J867) Inhibits Proliferation and Induces Apoptosis in Cultured Human Uterine Leiomyoma Cells in the Absence of Comparable Effects on Myometrial Cells

Abstract: Context: Asoprisnil, a selective progesterone (P4) receptor (PR) modulator (SPRM) with mixed P4 agonist/antagonist activities, reduces uterine leiomyoma volume in a dose-dependent manner in the presence of follicular phase estrogen concentrations. The evidence from clinical studies suggests that asoprisnil may directly target the uterine leiomyomata. Objective and Methods:The present study evaluated the effects of asoprisnil on cell proliferation, the expression of apoptosis-related proteins, and apoptosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 42 publications
2
75
0
2
Order By: Relevance
“…Further studies have demonstrated that asoprisnil reduces volume of uterine fibroids in a dose dependent manner [30] . Similarly in vitro studies have shown Asoprisnil (As) inhibits proliferation and induces apoptosis in cultured human uterine leiomyoma cells in absence of similar effect in myome-trial cells [34] . Just like in nonhuman primates Asoprisnil (As) was associated with decrease in proliferation markers Ki 67 while PTEN (Phosphatase and tensin homologue) a tumour suppressor gene expression remained unaltered ,in patients receiving 10/25 mg asoprisnil, thus making it a safe option [31] .…”
Section: Role Of Asoprisnilmentioning
confidence: 97%
“…Further studies have demonstrated that asoprisnil reduces volume of uterine fibroids in a dose dependent manner [30] . Similarly in vitro studies have shown Asoprisnil (As) inhibits proliferation and induces apoptosis in cultured human uterine leiomyoma cells in absence of similar effect in myome-trial cells [34] . Just like in nonhuman primates Asoprisnil (As) was associated with decrease in proliferation markers Ki 67 while PTEN (Phosphatase and tensin homologue) a tumour suppressor gene expression remained unaltered ,in patients receiving 10/25 mg asoprisnil, thus making it a safe option [31] .…”
Section: Role Of Asoprisnilmentioning
confidence: 97%
“…In this case, the PR ligand complex presents only one different conformation as compared to that of 12. This fact could explain why 10 was more effective than 12 or 13 by considering the presence of co-activators 35,36 . On the bases of their effect as pure antagonist, different types of PR antagonists were identified and described; this prevents the binding of PR complex to DNA (13, Figure 4) [32][33][34] .…”
Section: Crystallographic Studies Of Pr Leading To the Design Of New mentioning
confidence: 99%
“…On the bases of their effect as pure antagonist, different types of PR antagonists were identified and described; this prevents the binding of PR complex to DNA (13, Figure 4) [32][33][34] . Partial antagonists are those which facilitate the binding of the ligandjoin PR to the progesterone response element (PRE) present in DNA helix; however, they show also an agonistic activity in the target tissues (12, 11, Figure 3) 35 . The antiproliferative activity of steroid 10 ( Figure 4) is explained on the ground that this steroid can attach to the ligand binding domain of PR, a helix 12 conformation.…”
Section: Crystallographic Studies Of Pr Leading To the Design Of New mentioning
confidence: 99%
“…It induces amenorrhea and reduces uterine fibroid volume in a dose-dependent manner [54,55], and it reduces uterine artery blood flow [56]. Asoprisnil has marginal abortifacient activity and no antiglucocorticoid effect [57][58][59][60]. This drug does not induce estrogen deprivation symptoms or breakthrough bleeding.…”
Section: Selective Progesterone Receptor Modulatorsmentioning
confidence: 99%